PENGARUH KEPEMIMPINAN KEPALA SEKOLAH DAN PENINGKATAN PROFESIONAL GURU TERHADAP KINERJA GURU DI MASA PANDEMI COVID-19 - Yunus Russamsi; Hanhan Hadian; Acep Nurlaeli (MANAGERE : Indonesian Journal of Educational Management, 2020)
Process during the Covid-19 pandemic which was carried out at home in accordance with a government circular in order to break the chain of the spread of Covid 19. "Unpreparedness of all elements, one of which is that teachers in learning are a big obstacle too, there is a change in teaching and learning from Being face-to-face being online requires readiness from all elements. Therefore, the leadership of school principals and teacher professionals are two factors among other factors that can affect teacher performance during the Covid-19 pandemic. This study used a quantitative approach with a survey method with a total sample of 42 teachers. The data collection technique used a questionnaire with a Likert scale. Data were analyzed using simple and multiple correlation and regression techniques. The results showed that the influence of the principal's leadership and professional teachers was very dominant on the teacher's performance at SD Asy-Syifa 2 Bandung with a level of influence of 52.1%, and the remaining 47.9% was determined by other factors. So it can be concluded that the better the leadership of the principal and the professional improvement of teachers, the better the teacher's performance.